Peak Power Reduction Using Improved Selective Mapping Technique for OFDM - Muhmmad Rizwan Anjum; Mussa A. Dida; M. A. Shaheen (Institute of Advanced Engineering and Science, 2014)
OFDM has Major disadvantage is that it leads to high Peak to Average Power Ratio (PAPR) which is consider to be as the main implementation drawback. In this paper we are discussing about PAPR which affects the performance and efficiency of Power Amplifier (PA) and its influence by utilizing the Selective Mapping (SLM) technique in OFDM system for reduction of PAPR. the idea for improved SLM produces several independent signals based on converting the original data lock into many independent signal and then the signal has lowest PAPR that specific signal is transmitted. Also data rate trade-off exist at the receiver end when side information is detected for the recovery of data block. which leads to the reduction of data rate. Improved SLM techniques for reducing the PAPR is the most promising reduction technique in its non-uniform phase factor for PAPR reduction in multicarrier OFDM system. Furthermore the estimate expression by using Complementary Cumulative Distribution Function (CCDF) for PAPR has been discussed. Simulated results demonstrate that OFDMA signals using improved SLM technique carried significant effects in reduction of PAPR in OFDM system.